Analisis Efektifitas Daya Tampung Embung Daerah Irigasi Anggotoa Kabupaten Konawe - Maladeni, Eva Safitri (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
Water is very important in an irrigation area. In the growth of plants such as rice, they really need an adequate amount of water, so there is a need for research on effectiveness in terms of water requirements and in terms of water availability in irrigation buildings such as reservoirs. The purpose of this study was to determine the level of effectiveness of the availability of water in Embung Anggotoa in supplying water needs in the fields of Kukuluri Village. In this study, a modified Penman method was used to calculate the level of water use by plants, then calculated the need for clean water in the fields and then compared with the availability of water in the fields. the member pond. In analyzing the availability of water in the Anggotoa reservoir, a minimum discharge calculation is used using the Rational method. The results of the analysis of the need for clean water in the fields based on effective rainfall data and climatological data analyzed resulted in the water demand in the fields of 10.4605 mm/day/ha, then multiplied by the land area to determine the overall discharge required in Kukuluri rice fields with a land area of ​​95 ha. then the result is 993.7475 mm3/day. The results of the analysis of the minimum discharge in the upstream of the Anggotoa Reservoir based on rainfall data using the Rational method for a return period of 2 years = 61.198 m3/s, a return period of 5 years = 74,899 m3/s, a return period of 10 years = 87,686m3/s, a return period of 20 years = 100.930 m3/s, return period of 25 years = 105.041m3/s, return period of 50 years = 117.828, and return period of 100 years = 130.616 m3/s. Based on the results of the analysis of the flow of water availability, it shows that the capacity of the Anggotoa reservoir is still effective in meeting the water needs of the Kukuluri rice fields, the current accommodated discharge reaches 99405 m3 from the initial planning of 100000 m3.